Diagnosing bipolar disorder with the diagnostic interview for psychoses (DIP) : a reliability study - Skorven, Caroline Spant; Mikalsen, Guro (Universitetet i Tromsø, 2010)
A reliability study of the Norwegian translation of the Diagnostic Interview for Psychoses (DIP) was conducted, with a focus on its usefulness when diagnosing bipolar disorder. Emphasis is given to the severity and importance of correct diagnosis and treatment of this disorder. The DIP is a semi-structured interview that aims to assess low prevalent psychiatric disorders. It is based on the Operational Criteria for Psychoses (OPCRIT), and generates diagnoses according to several diagnostic systems. The respondents included in the study were inpatients at the psychiatric hospitals in Tromsø and Bodø. Twenty-seven respondents were independently assessed by two raters, one of whom conducted the interview, while the other scored from observation. Fourteen of them were re-interviewed later by a third independent rater. Inter-rater reliability was generally high, with good to excellent agreement on the majority of items. Agreement on broad diagnostic categories was also high. Test-retest reliability for both individual items and broad diagnostic categories ranged from moderate to excellent. The findings are consistent with the results of previous studies of the reliability of DIP. The results reported here are based on preliminary data from a lager research project, and should be viewed with some caution. The findings and their possible implications are discussed in relation to bipolar disorder and the conceptualisation of this, and other, severe mental disorders.